PENGARUH PENERAPAN EXPERIENTIAL MARKETING TERHADAP LOYALITAS KONSUMEN KARTU PRA BAYAR SIMPATI TELKOMSEL (JURNAL ECONOMICA : Research of Economic And Economic Education, 2012)
This research aims to analyze influences of experiential marketing variable as dependent variable and provides consumer experiences in getting benefit from communication services to simPATI consumer loyalty. This research is descriptive research with non probability sampling technique – convenience sampling method. Sample size is Hair income that is 20 times of variable, number of respondent is 100 people. The data is analyzed by using multiple regressions with SPSS program, test, F test, alpha 0.05. The research shows, (1). No significant influences between sense marketing and customer loyalty (sig=0.166). (2). There is significant influences between feel marketing and customer loyalty (Sig = 0.029). (3). No significant influences between feel marketing and customer loyalty (Sig = 0,689). (4). There is a significant influence between act marketing and customer loyalty. (5). No significant influences between relate marketing and customer loyalty (Sig = 0,572). (6). There is a significant influence between all variables experiential marketing and customer loyalty (Sig = 0,000). Researcher suggests company to review sense marketing, act marketing and relate marketing strategy that has applied and consider other factors that influences consumer loyalty and also increase feel marketing and think marketing strategies.